Financing Patterns around the World : The Role of Institutions - Beck, Thorsten (World Bank, Washington, DC, 2014)
Using a firm-level survey database covering 48 countries, the authors investigate whether differences in financial and legal development affect the way firms finance their investments. The results indicate that external financing of investments is not a function of institutions, although the form of external finance is. The authors identify two explanations for this. First, legal and financial institutions affect different types of external finance in offsetting ways. Second, firm size is an important determinant of whether firms can have access to different types of external finance. Larger firms with financing needs are more likely to use external finance compared with small firms. The results also indicate that these firms are more likely to use external finance in more developed financial systems, particularly debt and equity finance. The authors also find evidence consistent with the pecking order theory in financially developed countries, particularly for large firms.